Antibiofilm Activity of Nystatin, Aspirin and EDTA Against Candida albicans Isolated from Iraqi Women with Vulvovaginitis (Medico Legal Update, 2021)
The vulvovaginitis candidiasis is often associated with biofilm formation by Candida albicans and using ofantifungal agents against C. albicans biofilms is urgently needed. Microtiter plate assay using crystal violetwas used for detection the ability of Candida albicans to form biofilm and the microtiter broth dilutionmethod was used for determination the minimum inhibitory concentrations (MICs). Out of 42 Candidaalbicans isolated from vulvovaginitis, 37 (88%) can produce biofilm at the varying degrees. Twenty-eight(75.7%) isolates could form a strong biofilm. The results of minimum inhibitory concentrations (MICs) ofNystatin, Aspirin and EDTA (Ethylenediaminetetraacetic acid) against 28 C. albicans isolates which formedthe strong biofilm, revealed that range of concentrations of Nystatin were (6.25-100 µg/ml), while the MICsof aspirin and EDTA were more than 1000 µg/ml. It was obvious that the Nystatin had the inhibitory activityat the concentrations 6.25 and 12.5 µg/ml. The highest antibiofilm activity by Nystatin were demonstratedat the subinhibitory concentration 50 ?g/ml with biofilm eradication percent (75.80%), while the lowestantifungal effect (2.86-10.70%) was at very low concentrations (3.125-6.25 ?g/ml). Also, there was anobvious biofilm eradication of Aspirin and EDTA at the concentrations 500 and 1000 ?g/ml but the effectof aspirin at the concentration 1000 ?g/ml (70.51%) is more than EDTA (60.12%) in contrast with theconcentration 500 ?g/ml, it was found that the effect of EDTA (51.29%) is more than aspirin (34.25%). Inconclusion, the present study highlights the role of Aspirin and EDTA as antibiofilm agents when used withNystatin which have the ability to inhibit the growth of C. albicans in patients with vulvovaginitis.